POTENSI SPERMIOSIDA SAPONIN EKSTRAK DAUN SIRSAK (ANNONA MURICATA L.) DITINJAU DARI JUMLAH SPERMATOZOA MENCIT (MUS MUSCULUS BALB/C) ALBINO JANTAN - Silvi Hidayatul Kamilah (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2020)
Soursop leaf (Annona muricata L.) is a plant that is often used as medicine of the community. Soursop leaves contain saponin compounds. Saponins are known to be spermiosides which can affect the process of spermatogenesis which causes a decrease in the number of spermatozoa. Right Diagnosis from Healthgrades 2015 shows the prevalence of South Asian men infertility that Vietnam as the first with a total of 1,853,834 people, then Indonesian 1,753,330 people, and the Philippines in the third with the number 643,130 people. The purpose of this study was to determine the effect of graded soursop leaf extract saponins on the number of spermatozoa of male albino mice (Mus Muculus Balb/c). This study uses an a Post Test Control Group Design research design using experimental animals male albino mice (Mus musculus babl/c). Divided into 4 groups, the control group was P1 at a dose of 14mg / KgBB, P2 at 28mg / KgBB, and P3 at 56mg / KgBB. This research was conducted in 21 May-05 June 2019 in the anatomy laboratory of STIKes Piala Sakti Pariaman. The sampling technique uses Purpose Sampling technique with a sample of 24 mice. One Way Anova test results showed the effect of soursop leaf extract (Annona muricata L.) on the decrease in the number of spermatozoa with a p value of 0.000 then continued with the Post Hock LSD test to find out significant differences between groups. The results showed that soursop leaf extract can reduce the number of spermatozoa of mice with the value of the control group 7.63±0.05, P1 7.43±0.05, P2 7.26±0.05, P3 7.13±0.05. Need to do further testing on humans as an effort to test the safety of doses.